2010
DOI: 10.1007/s00280-009-1223-2
|View full text |Cite
|
Sign up to set email alerts
|

Semi-mechanistic population pharmacokinetic/pharmacodynamic model for neutropenia following therapy with the Plk-1 inhibitor BI 2536 and its application in clinical development

Abstract: Purpose (1) To describe the neutropenic response of BI 2536 a polo-like kinase 1 inhibitor in patients with cancer using a semi-mechanistic model. (2) To explore by simulations (a) the neutropenic effects for the maximum tolerated dose (MTD) and the dose at which dose-limiting toxicity occurred, (b) the possibility to reduce the cycle duration without increasing neutropenia substantially, and (c) the impact of the initial absolute neutrophil count (ANC) on the degree of neutropenia for different doses. Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
(51 reference statements)
1
18
0
Order By: Relevance
“…Because BI 2536 induces cell-cycle arrest and apoptosis, systemic effects, such as hematotoxicity, cellular depletion of the bone marrow, and gastrointestinal effects, may be explained by the pharmacologic activity of the drug. Although no pharmacodynamic endpoints were analyzed as part of this study, neutropenia is a characteristic side effect observed with mitotic inhibitors and may be seen as a surrogate for target inhibition by BI 2536 (12).…”
Section: Discussionmentioning
confidence: 99%
“…Because BI 2536 induces cell-cycle arrest and apoptosis, systemic effects, such as hematotoxicity, cellular depletion of the bone marrow, and gastrointestinal effects, may be explained by the pharmacologic activity of the drug. Although no pharmacodynamic endpoints were analyzed as part of this study, neutropenia is a characteristic side effect observed with mitotic inhibitors and may be seen as a surrogate for target inhibition by BI 2536 (12).…”
Section: Discussionmentioning
confidence: 99%
“…This model has since the original publication been successfully applied to both leukocyte and neutrophil measurements following several additional anti-cancer drugs and regimens [6][7][8][9][10][11][12][13][14][15][16]. It has also been shown to satisfactorily describe thrombocyte and lymphocyte measurements following chemotherapy [17][18][19].…”
Section: Introductionmentioning
confidence: 98%
“…Toxicity in these animals was limited to a significant reduction in the numbers of neutrophils in the bone marrow ( Supplementary Fig. 1), which is the most common side effect described in humans following treatment with BI 2536 (18,19).…”
Section: Bi 2536 Treatment Induces Cell Death Via Apoptosismentioning
confidence: 99%